The design and implementation of mission-oriented innovation policies A new systemic policy approach to address societal challenges - Larrue, Philippe (OECD Science, Technology and Industry Policy Papers, 2021)
This paper analyses 'mission-oriented innovation policies' (MOIPs), a new type of systemic intervention that a growing number of countries has implemented in order to tackle mounting societal challenges. These policies aim to alleviate some of the most prevalent weaknesses within many national systems of innovation, notably the lack of holistic strategic orientation and policy co-ordination, and fragmented policy mixes. This paper leverages a dedicated analytical framework to systematically explore the challenges and opportunities that these policies present at initiative and country levels. In doing so, it provides a better understanding of the different ways in which governments design, fund and coordinate MOIPs, and contributes to broadening the range of options available to either improve or initiate this policy approach. This paper complements the MOIP Online Toolkit (https://stip.oecd.org/stip/moip), the OECD knowledge platform on MOIPs